Dutrapona, a new genus and three new species of Gyponini (Insecta: Hemiptera: Cicadellidae) from Central and South America - Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2024)
A new leafhopper genus of the tribe Gyponini, Dutrapona gen. nov., is proposed and described based on males of three newly described species from Central and South America: Dutrapona tenuis sp. nov. (type species) from Alajuela, Costa Rica, Dutrapona reticulata sp. nov. from Napo, Ecuador, and Dutrapona zahniseri sp. nov. from Coclé, Panama. The new genus resembles genera of the Hecalapona complex in sharing characteristics such as: body yellow without maculae and dorsoventrally flattened, crown moderately produced with anterior margin rounded and projected over anterior margins of eye, crown-face transition distinct and thin, maxillary plates narrow and not extending to clypeus apex and forewing with narrow appendix. However, Dutrapona gen. nov. can be distinguished from other Gyponini genera by the combination of the following of characteristics: ocelli positioned closer to midline and posterior margin of the crown, crown-face transition spatulate with two well defined carinae, male sternite VIII longer than wide, male pygofer with a pair of small caudal denticulated processes, subgenital plates short, and aedeagus with a pair of basilateral elongate processes.